A nondualistic Pentecostal theology: exploring dialectics and becoming through Amos Yong and Slavoj žižek - Moffat, Spencer (Lexington Books, Fortress Academic, 2025)
"This work examines the contradiction between Amos Yong's philosophical nondualism and theological dualism and Slavoj Žižek's Hegelian dialectics. What emerges is a nondualistic pentecostal theology that identifies the God-World relationship as inextricable, dialectics being driven by negativity, and transcendence as the creative act"--